The endosomal sorting complex required for transport repairs the membrane to delay cell death - Yang, Ye; Wang, Min; Zhang, Ying-Ying; Zhao, Shu-Zhi; Gu, Song (Frontiers in Oncology, 2022)
The endosomal sorting complex required for transport (ESCRT) machinery plays a key role in the repair of damaged plasma membranes with puncta form and removes pores from the plasma membrane in regulated cell death, apoptosis, necroptosis, pyroptosis, ferroptosis, and autophagy. ESCRT-I overexpression and ESCRT-III-associated charged multivesicular body protein (CHMP) 4B participate in apoptosis, and the ESCRT-1 protein TSG 101 maintains low levels of ALIX and ALG-2 and prevents predisposition to apoptosis. The ESCRT-III components CHMP2A and CHMP4B are recruited to broken membrane bubble sites with the requirement of extracellular Ca2+, remove membrane vesicles from cells, and delay the time required for active MLKL to mediate necroptosis, thus preserving cell survival. CHMP4B disturbed pyroptosis by recruiting around the plasma membrane neck to remove the GSDMD pores and preserve plasma membrane integrity depending on Ca2+ influx. The accumulation of the ESCRT-III subunits CHMP5 and CHMP6 in the plasma membrane is increased by the classical ferroptosis activators erastin-1 and ras-selective lethal small molecule 3 (RSL3) upon cytosolic calcium influx and repairs the ferroptotic plasma membrane. ESCRT-III- and VPS4-induced macroautophagy, ESCRT-0-initiated microautophagy. ESCRT-I, ESCRT-II, ESCRT-III, ALIX, and VPS4A are recruited to damaged lysosomes and precede lysophagy, indicating that ESCRT is a potential target to overcome drug resistance during tumor therapy.